Estudo das estratégias dos complexos convectivos de mesoescala no Nordeste brasileiro entre os anos de 1999 e 2009 - Albuquerque, Carolina Silva Miranda de (2013)
The main objective of the study was to analyze the trajectories of Mesoscale Convective Complexes (MCC) in Northeast Brazil (NEB) in the period 1999-2009, beyond the development of a short time predict model to the displacement of the events. The influence of potential temperature and absolute humidity in the displacement of the events, and the development of a mathematical model that can help predict the trajectories of the same. We used data from the Meteosat satellites and Goes, the infrared channel, assisted in the location of events. Through the National Centers for Environmental Prediction NCEP and the National Center for Atmospheric Research NCAR data were obtained from the potential temperature, absolute humidity and zonal and meridional components of the wind, which were analyzed for their influence on the displacement of CCMs. With these data, equations were developed, with linear regression, to help predict the trajectories of the MCCs. Most events shifted toward strong potential temperature gradients. These during the summer tended to move to cooler regions, if compared to the development region. During the fall, contrary, the events went to regions of higher temperature. MCCs that followed for colder regions had same trajectories wind direction at middle and senior levels. Nuclei of absolute humidity were observed in 58 cases, the majority of this level of 1000 hPa. MCCs tended to move to lower- UA. When events went to lower UA, they were likely to follow the wind direction at low levels and high levels when moved toward greater UA.The developed mathematic model don’t presented satisfactory precision to predict the trajectory of the events. Therefore, the PT and the AU, together with the wind, are factors that contributed in the trajectory of the MCCs, and the PT is the studied variable that has the biggest influence in the trajectories of the events.